Retirement Preparation of Public School Teachers in the District of Jalajala - Besanes, Margarette Micah (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the retirement preparation of public school teachers in the District of Jalajala, Rizal, focusing on well-being, lifestyle, and financial security readiness. It employed a descriptive survey research design using a researcher-made questionnaire administered to 145 public school teachers from elementary and secondary schools. Respondents were described according to age, sex, civil status, length of service, educational attainment, position title, and in-service trainings attended. Findings revealed that most respondents were 41–50 years old, female, married, bachelor’s degree holders, Teacher I, and had 6–10 years of service. They were moderately prepared in terms of well-being, lifestyle, and financial security. Significant differences were found according to civil status and length of service, while other variables showed no significant differences. Teachers commonly experienced limited access to financial literacy and retirement preparation programs. The study concluded that demographic factors generally do not influence retirement preparation, except for specific variables related to civil status and service length. It is recommended that schools implement structured retirement programs, strengthen financial literacy initiatives with agencies such as the Government Service Insurance System, and provide counseling and wellness support. Teachers are encouraged to engage in early financial planning, develop healthy post-retirement lifestyles, and seek updated information on retirement processes and benefits. Overall, the study highlights the need for proactive and continuous retirement preparation among public school teachers. These findings suggest that retirement readiness is a multidimensional process that requires institutional support, continuous professional education, and personal accountability to ensure a smooth transition from active service to retirement life among educators. Strengthening collaboration among school leaders, teachers, and government agencies is essential in addressing gaps in financial preparedness, emotional well-being, and lifestyle adjustment, thereby promoting sustainable retirement outcomes and enhancing the overall quality of life of retiring educators in the district of Jalajala Rizal Philippines setting respectively contextually
Keywords: Retirement Preparation, Public School Teachers, Financial Security, Well-Being, Lifestyle Adjustment, Descriptive Survey, Jalajala, Retirement Readiness